Day 1 Mon, February 04, 2013 2013
DOI: 10.2118/163846-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Horizontal Wells in the Eagle Ford Using Oil-Based Chemical Tracer Technology to Optimize Stimulation Design

Abstract: Horizontal well positioning through a target formation can have a significant impact on overall productivity from an unconventional oil well. This paper will discuss the evaluation of two horizontal wells completed in the oil section of the Eagle Ford Shale. These wells were completed using similar completion designs (hybrid frac design) with the method and number of frac stages determined by the geology, petrophysical, or geomechanical data. The paper will describe how conventional analysis tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Since fracture closure was not modeled in these simulations, almost 100% recovery of the injected tracer was observed during flowback. However, several field studies have shown very low tracer recovery [19,20,37]. The tracer retention due to fracture closure can help in understanding the low tracer recovery, which is explained in the next section.…”
Section: Normalized Tracer Concentration (C D ) =mentioning
confidence: 99%
See 1 more Smart Citation
“…Since fracture closure was not modeled in these simulations, almost 100% recovery of the injected tracer was observed during flowback. However, several field studies have shown very low tracer recovery [19,20,37]. The tracer retention due to fracture closure can help in understanding the low tracer recovery, which is explained in the next section.…”
Section: Normalized Tracer Concentration (C D ) =mentioning
confidence: 99%
“…Figure19. Fractures in a complex fracture network categorized based on the connectivity of a fracture to the wellbore.…”
mentioning
confidence: 99%
“…The use of chemical tracers in unconventionals can provide information about the relative effectiveness of hydraulic factures. Chemical tracers can also be used to examine stage or interval contribution over time (Catlett et al 2013). From a reservoir characterization standpoint, tracer technology has the potential to provide "ground truth" geological interpretations.…”
Section: Chemical Tracer Datamentioning
confidence: 99%
“…Tracers are powerful diagnostic tools in numerous scientific disciplines and in many fields of industrial technology 1–6 . Meanwhile, these had broad application prospects in the field of oil fields 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…Tracers are powerful diagnostic tools in numerous scientific disciplines and in many fields of industrial technology. [1][2][3][4][5][6] Meanwhile, these had broad application prospects in the field of oil fields. [7][8][9] The tracers can return the underground situation to the ground through signals, which can better assist in the field survey of oil reservoirs (including inter-well connections, inter-layer connections and heterogeneity).…”
Section: Introductionmentioning
confidence: 99%